Basic psychoradiology: A brief review [Temel psikoradyoloji: Kısa bir gözden geçirme] - (:unkn) unknown (Istanbul Universitesi, 2017)
Psychoradiology, a newly developing field at the intersection of psychiatry and radiology, and based on foundations of neuroscience and neuroimaging, primarily targets to quantitatively define patterns of structural and functional brain aberrations in psychiatric disorders by utilizing non-inva-sive medical imaging methods. Psychoradiology studies appear significantly more frequent in current psychiatry and neuroscience literature. This manuscript aims to briefly explain three commonly used imaging techniques, summarize capabilities and limitations of respective deductive analytic models, and cite future directions and potential utilities of psychoradiology. © 2017, Istanbul Universitesi. All rights reserved.
Keywords: Diffusion tensor imaging; Functional magnetic resonance imaging; Neuroimaging; Psychoradiology; Voxel based morphometry